KANDUNGAN ALUMINIUM DALAM KALENG BEKAS DAN PEMANFAATANNYA DALAM PEMBUATAN TAWAS - Manurung, Manuntun; Ayuningtyas, Irma Fitria (Jurnal Kimia (Journal of Chemistry); Vol. 4, No. 2 Juli 2010, 2012)
This research was performed to analyze the aluminium content in several wasted cans. The analysis used AAS at 309.3 nm. This method was chosen since its operation is relatively simple but capable of analyzing low metal contents (less than 1 ppm). The aluminium content of wasted cans ranges from 1.41% up to 16.04%. The aluminium was used to make alum, with the percentage of yield of 77.04% up to 96.81%, depending on the type or cans. In other words, one gram of wasted cans produced 0.2335 grams up to 2.6857 grams of alum. The produced alum was capable of purifying water.
Keywords: aluminium, alum, atomic absorption spectrophotometer